2022
DOI: 10.1038/s42003-022-04042-z
|View full text |Cite
|
Sign up to set email alerts
|

Vascular smooth muscle RhoA counteracts abdominal aortic aneurysm formation by modulating MAP4K4 activity

Abstract: Whether a small GTPase RhoA plays a role in the pathology of abdominal aortic aneurysm (AAA) has not been determined. We show here that RhoA expression is reduced in human AAA lesions, compared with normal areas. Furthermore, incidence of AAA formation is increased in vascular smooth muscle cell (VSMC)-specific RhoA conditional knockout (cKO) mice. The contractility of the aortic rings and VSMCs from RhoA cKO mice is reduced, and expression of genes related to the VSMC contractility is attenuated by loss of Rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The liver isolated from a dead monkey was homogenized mechanically in radioimmunoprecipitation assay (RIPA) buffer (50 mmol/L Tris–HCl [pH 7.5], 150 mmol/L NaCl, 0.5% sodium deoxycholate, 0.1% sodium dodecyl sulfate (SDS), 1% Nonidet P-40, 1 μg/mL aprotinin, 1 μg/mL leupeptin, 1 mmol/L phenylmethylsulfonyl fluoride, 5 mmol/L sodium fluoride, and 1 mmol/L sodium orthovanadate) 59 . The lysates were centrifuged at 14,000 rpm for 15 min, and the supernatant was used for further experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The liver isolated from a dead monkey was homogenized mechanically in radioimmunoprecipitation assay (RIPA) buffer (50 mmol/L Tris–HCl [pH 7.5], 150 mmol/L NaCl, 0.5% sodium deoxycholate, 0.1% sodium dodecyl sulfate (SDS), 1% Nonidet P-40, 1 μg/mL aprotinin, 1 μg/mL leupeptin, 1 mmol/L phenylmethylsulfonyl fluoride, 5 mmol/L sodium fluoride, and 1 mmol/L sodium orthovanadate) 59 . The lysates were centrifuged at 14,000 rpm for 15 min, and the supernatant was used for further experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The EC transfection efficiency and specificity of AAV9 were confirmed by western blotting and immunofluorescence. For MAP4K4 inhibitor treatments, DMX-5804 (MCE, USA) was orally administered at a dose of 3 mg/kg three times per week at 4 weeks of age for 24 weeks [28].…”
Section: Animalsmentioning
confidence: 99%
“…To further validate the regulatory effects of MAP4K4 on SNO-Drp1, DMX-5804, a specific MAP4K4 inhibitor, was used [28]. DMX-5804 decreased MAP4K4 expression in HG/FFA-injured cells and db/db mice (Additional file 5: Fig.…”
Section: Map4k4-inducible Drp1 S-nitrosylation Promoted Ferroptosis B...mentioning
confidence: 99%
“…The mechanistic study revealed that MAP4K4 activity is crucial for muscle degeneration [ 98 ]. Interestingly, the MAP4K4 inhibitor DMX-5804 was able to reverse abdominal aortic aneurysms (AAAs) induced by loss of RhoA in vascular smooth muscle cells [ 99 ]. These preclinical findings suggest that MAP4K4 might be a viable target for cancer-associated cachexia.…”
Section: Role Of Map4k4 In Cancer Cachexiamentioning
confidence: 99%